Culturally Tailored Intervention to Promote Mammography Screening Practice Among Chinese American Women: a Systematic Review - Xuehui Zhang; Ping Li; Pingping Guo; Jie Wang; Na Liu; Shu Yang; Lin Yu; Xiumin Zhang; Wei Zhang (Journal of Cancer Education, 2020)

Valine acts as a nutritional signal in brain to activate TORC1 and attenuate postprandial ammonia-N excretion in Chinese perch (Siniperca chuatsi) - Jie Wang; Xu-Fang Liang; Shan He; Yan-Peng Zhang; Jiao Li; Kang Huang; Lin-Jie Shi; Ping Ren (Fish Physiology and Biochemistry, 2020)

Prevalence and Bayesian Phylogenetics of Enteroviruses Derived From Environmental Surveillance Around Polio Vaccine Switch Period in Shandong Province, China - Chenxu Zhao; Xiaojuan Lin; Feng Ji; Ping Xiong; Yao Liu; Suting Wang; Peng Chen; Qing Xu; Li Zhang; Zexin Tao; Aiqiang Xu (Food and Environmental Virology, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Genetic diversity analysis reveals new badnaviruses infecting banana in South China - Xue-Qin Rao; Zi-Lin Wu; Wan Wang; Lin Zhou; Jie Sun; Hua-Ping Li (Journal of Plant Pathology, 2020)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

2D slope stability analysis based on Pan’s maximum principle - Xiao Gang Wang; Xing Chao Lin; Ping Sun; Xu Li; Yu Jie Wang; Yong Yu Ling (Bulletin of Engineering Geology and the Environment, 2020)

Colletotrichum neorubicola sp. nov., a new leaf anthracnose pathogen of raspberry from northeast China - Li-Ping Liu; Yu Wang; Peng-Lei Qiu; Bo Zhang; Lin Zhang; Na Wang; Yu Li; Jie Gao; Tom Hsiang (Mycological Progress, 2020)

The protective effect of rosmarinic acid on myotube formation during myoblast differentiation under heat stress - Kun-Lin Chen; Yue Wang; Zhi-Ping Lin; Hui-Xia Li (In Vitro Cellular & Developmental Biology - Animal, 2020)

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Prenylated isoflavones with potential antiproliferative activities from Mappianthus iodoides - Yan-Ping Liu; Li-Li Sun; Xiang-Lin Zhang; Hai-Yuan Niu; Zheng-Hong Pan; Yan-Hui Fu (Natural Product Research, 2020)

Effect of Freezing and Thawing on Microstructure Damage and Dynamic Flexural Tension of Granite - Chuanju Liu; JunRen Deng; Songtao Yu; Ping Li; Yun Lin (Rock Mechanics and Rock Engineering, 2020)

Comparative analysis and natural evolution of squalene epoxidase in three Fritillaria species - Xu Lu; Lin-Ning Zhang; Jin-Fa Du; Xiao-Yan Zheng; Hui-Jun Li; Ping Li; Gui-Zhong Xin; Yan Jiang (Plant Molecular Biology, 2020)

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

High-level soluble expression of human Cu,Zn superoxide dismutase with high activity in Escherichia coli - Jin-Ling Yang; Xing-Lun Li; Feng-Lin Jiang; Ting Gong; Jing-Jing Chen; Tian-Jiao Chen; Ping Zhu (World Journal of Microbiology and Biotechnology, 2020)

Microseismic Monitoring to Characterize Structure-Type Rockbursts: A Case Study of a TBM-Excavated Tunnel - Quan-Sheng Liu; Jian Wu; Xiao-Ping Zhang; Lie-Xian Tang; Chen Bi; Wei-Wei Li; Jin-Lin Xu (Rock Mechanics and Rock Engineering, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

Biofertilizers with beneficial rhizobacteria improved plant growth and yield in chili (Capsicum annuum L.) - Jing-Yi Gou; Sheng-Zhou Suo; Kun-Zhong Shao; Qi Zhao; Dan Yao; Hui-Ping Li; Jin-Lin Zhang; Christopher Rensing (World Journal of Microbiology and Biotechnology, 2020)

Cognitive Load of Exercise Influences Cognition and Neuroplasticity of Healthy Elderly: An Exploratory Investigation - Yi-Ping Chao; Changwei W. Wu; Li-Jung Lin; Cheng-Hung Lai; Hong-Yi Wu; Ai-Ling Hsu; Chiao-Nan Chen (Journal of Medical and Biological Engineering, 2020)
This study explored the effects of exercise with either high cognitive load or low cognitive load on cognitive performance and neuroplasticity in healthy elderly. Twenty-eight sedentary community-dwelling seniors participated in this study. Participants were assigned to one of three groups: the control group (C), low-cognitive load exercise group (LE), or high-cognitive load exercise group (HE). Individuals in both exercise groups engaged in moderate-intensity aerobic exercise for 4 months. Resting-state functional MRI and diffusion MRI were used to investigate the effects of intervention on functional and structural connectivity, respectively. Analysis of covariance with baseline, age and the education year as covariates was used to determine the effects of intervention. We found 4 months of exercise with high-cognitive load, but not exercise with low-cognitive load, improved the overall cognitive function of healthy elderly. Additionally, the HE group showed increased resting-state functional connectivity of superior frontal gyrus and anterior cingulate cortex and decreased functional connectivity of middle occipital gyrus and postcentral gyrus. The age-related alterations in local efficiency and betweenness were protected by exercise. Our findings might suggest that exercise with greater cognitive load likely results in greater training effects on cognition and brain connectivity than exercise requiring lower cognitive loads for healthy elderly.

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

3D slope stability analysis method based on Pan’s maximum principle - Xiaogang Wang; Xinchao Lin; Xu Li; Ping Sun; Yongyu Ling (Landslides, 2020)

Ultraviolet photolysis of metformin: mechanisms of environmental factors, identification of intermediates, and density functional theory calculations - Wenting Lin; Xiaohan Zhang; Ping Li; Yongzhen Tan; Yuan Ren (Environmental Science and Pollution Research, 2020)

Advances in Urban Meteorological Research in China - Shiguang Miao; Weimei Jiang; Ping Liang; Hongnian Liu; Xuemei Wang; Jianguo Tan; Ning Zhang; Ju Li; Wupeng Du; Lin Pei (Journal of Meteorological Research, 2020)

Cytotoxic components from the Xisha sponge Fascaplysinopsis reticulata - Guo-Fei Qin; Xu-Li Tang; Nicole J. de Voogd; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2020)

Prolonged Neo-Tethyan magmatic arc in Myanmar: evidence from geochemistry and Sr–Nd–Hf isotopes of Cretaceous mafic–felsic intrusions in the Banmauk–Kawlin area - Jin-Xiang Li; Wei-Ming Fan; Li-Yun Zhang; Tou-Ping Peng; Ya-Li Sun; Lin Ding; Fu-Long Cai; Kyaing Sein (International Journal of Earth Sciences, 2020)

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

Two new phenolic glycosides from the seeds of Citrullus lanatus - Xiao-Qian Zhang; Jing Shi; Shi-Xiu Feng; Lin Xue; Li-Ping Tian (Natural Product Research, 2020)

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

Molecular characterization of the Krüppel-homolog 1 and its role in ovarian development in Sogatella furcifera (Hemiptera: Delphacidae) - Kui Hu; Ping Tian; Lu Yang; Yan Tang; Lin Qiu; Hualiang He; Wenbing Ding; Youzhi Li (Molecular Biology Reports, 2020)

Effects of Starvation on Antioxidant-Related Signaling Molecules, Oxidative Stress, and Autophagy in Juvenile Chinese Perch Skeletal Muscle - Ping Wu; Aimin Wang; Jia Cheng; Lin Chen; Yaxiong Pan; Honghui Li; Qi Zhang; Jiaqi Zhang; Wuying Chu; Jianshe Zhang (Marine Biotechnology, 2020)

Nocardia panacis sp. nov., a novel actinomycete with antiphytopathogen activity isolated from the rhizosphere of Panax notoginseng - Jia-Yun Hu; Lei Li; Guang Peng; Yi-Qing Li; Li-Hua Xu; Hui-Lin Guan; Li-Xing Zhao; Cui-Ping Miao (Antonie van Leeuwenhoek, 2020)

Mechanistic examination of methimazole-induced hepatotoxicity in patients with Grave’s disease: a metabolomic approach - Xuesong Li; Jialin Yang; Shasha Jin; Yu Dai; Yujuan Fan; Xiaofang Fan; Zhigang Li; Jianhua Yang; Wai-Ping Yau; Haishu Lin; Weimin Cai; Xiaoqiang Xiang (Archives of Toxicology, 2020)